How do we perceive Characters? An Analysis of Human Perception in Still Images, Animations and VR Scenarios - Araujo, Victor; Dalmoro, Bruna; Geiss, Rafael; Pinho, Márcio S.; Musse, Soraia R. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2022: Anais Estendidos do XXI Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2022.225436, 2022)
Virtual characters can elicit an uncomfortable sensation usually known as Uncanny Valley (UV). Evidence suggests that animation exacerbates the UV effect. This paper revisits the UV hypothesis to assess its effects on people’s perception of virtual characters, to try to answer the questions “What happens to the perceptual comfort if, in addition to images and videos of characters, we include those characters in an interactive Virtual Reality (VR) environment?”, and “Considering the VR environment, do people feel equally comfortable if we increase the number of characters?”. The results indicate that there are differences in the perception of scenarios with low and high densities.